Food Supply Chain And Food Security During the Covid-19 Pandemic - Veranus Sidharta (FISIP UPNVJ, 2020)
The Coronavirus 2 (COVID-19) outbreak in Wuhan China at the end of 2019 has caused an epidemic of infectious diseases globally. This outbreak has a negative impact on almost all sectors including the food supply chain system sector, which raises concerns about food security due to social distance policies that tend to limit movement and contribute to disrupt food distribution. This study aims to analyze the structure of the communication network that is an obstacle in the food supply chain network the impact of the COVID-19 outbreak. The method used in this study is qualitative by using a constructivism paradigm and the data used are secondary data sourced from Literature Review data. The results of the study show that the communication network on the wheel structure is effective in resolving supply chain problems and food security during the COVID-19 pandemic, where the availability of staple food for rice and sugar for March to August 2020 is in a safe position with details of 23.2 tons of rice stock with surplus of 7.4 tons, sugar of 2.9 tons with a surplus of 1.4 tons.